2022
DOI: 10.1021/acs.chemmater.2c00293
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Surface Passivation of Lead Sulfide Quantum Dots for Short-Wavelength Photodetectors

Abstract: Lead sulfide (PbS) quantum dots are promising solution-processed materials for short-wave infrared (SWIR) photodetectors due to their tunable band gap and solution processability. Phase-transfer ligand exchange is a common method to prepare quantum dot (QD) inks used in device fabrication. For large-sized PbS QDs used for SWIR detection, the conventional phase-transfer ligand exchange has been problematic due to the densely packed organic ligands and charge-neutral (100) facets.Here, we report a new strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Under a given irradiance, the V oc decreases when the barrier height increases. The results in Figures a,b agree with studies that have shown that increasing ligand passivation by employing two-step instead of one-step ligand-exchange or by using a different ligand (methylammonium acetate vs ammonium acetate) leads to an increase in forward bias current.…”
supporting
confidence: 87%
“…Under a given irradiance, the V oc decreases when the barrier height increases. The results in Figures a,b agree with studies that have shown that increasing ligand passivation by employing two-step instead of one-step ligand-exchange or by using a different ligand (methylammonium acetate vs ammonium acetate) leads to an increase in forward bias current.…”
supporting
confidence: 87%
“…[23] MaAc can bind to the vacant sites of the III-V CQDs, given that a small positive ammonium ion and negative acid moiety would make an efficient co-passivation of the CQDs. [18,24] Hence, to maximize the effect of co-passivation, we introduce MaAc in the final-step solution ligand exchange to treat the unpassivated surface sites leftover after the standard InBr 3 /NH 4 Br exchange step, see schematics summarizing the ligand exchange reaction in Figure 2a. We compare the results of InAs CQDs capped with MaAc (MaAc-doped) to those of InAs CQDs samples (standard)-without adding MaAc, to study the effect of the co-passivation.…”
Section: Resultsmentioning
confidence: 99%
“…[8,[34][35][36][37] One notable advantage of CQDs is their design flexibility, not limited to chemical composition [38][39][40][41] but, more importantly, to size [42,43] and surface chemistry. [44][45][46][47] One of the workhorses of the field is lead-sulfide-based nanocrystals, PbS CQDs, because of their highly reproducible chemistry and their broad tunability (from the visible to the short wavelength infrared) of the absorption. [48][49][50] Colloidal quantum dots have been applied in various neuromorphic devices: in transistor architecture [8,51,52] as an additional charge-trapping layer within the dielectric and in two-terminal devices.…”
Section: Doi: 101002/aisy202300218mentioning
confidence: 99%
“…[ 8,34–37 ] One notable advantage of CQDs is their design flexibility, not limited to chemical composition [ 38–41 ] but, more importantly, to size [ 42,43 ] and surface chemistry. [ 44–47 ] One of the workhorses of the field is lead‐sulfide‐based nanocrystals, PbS CQDs, because of their highly reproducible chemistry and their broad tunability (from the visible to the short wavelength infrared) of the absorption. [ 48–50 ]…”
Section: Introductionmentioning
confidence: 99%